Barriers and facilitators to cervical cancer screening uptake among women in Nepal – a qualitative study. Issue 9 (20th October 2020) - Greibe Andersen, Johanne; Shrestha, Aamod Dhoj; Gyawali, Bishal; Neupane, Dinesh; Kallestrup, Per
ABSTRACT: The global incidence of cervical cancer is approximately 570, 000 cases and 311, 000 deaths annually. Almost 90% of cervical cancer deaths occur in low and middle income countries. Screening is the most effective tool in prevention, early diagnosis, and treatment of cervical cancer. Nepal has no national cervical cancer screening programme, and data from 2003 showed that only 2.8% of Nepalese women had ever been screened. We conducted a qualitative study to obtain better insight into barriers and facilitators to cervical cancer screening among women in Nepal to generate data to inform interventions. In February 2019, four focus group discussions with previously screened and non-screened women, and Female Community Health Volunteers and four in-depth interviews with health workers were conducted in Pokhara Metropolitan City. Semi-structured interview guides were used, interviews were audio-recorded, transcribed verbatim, and analyzed using grounded theory approach with open coding. This resulted in five main themes: 1) lack of husband's support for screening, 2) prevalent stigma and discrimination, 3) lack of awareness about screening options, 4) getting screened, and 5) health care providers. We encourage policymakers and stakeholders apply these findings to improve awareness, access to information, and better screening services in Nepal.